2014
DOI: 10.1684/abc.2014.0975
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between pharmacokinetic parameters of carbamazepine and therapeutic response in patients with bipolar disease

Abstract: This study aimed to assess the relationship between plasma levels of carbamazepine and its active metabolite 10,11-epoxide-carbamazepine, and the therapeutic response in patients with bipolar disease. Thirteen patients were kept on a fixed individual dose of carbamazepine for 19 weeks under psychiatric care. Steady-state plasma concentrations of carbamazepine and its metabolite 10,11-epoxide-carbamazepine were measured at weeks 4, 12, and 20 by HPLC essay. Simultaneously, the psychopathologic state was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In a previous study, a similar result was found in a group of patients with bipolar disorder who were treated with CBZ [ 17 ]. As evaluated by the Brief Psychiatric Rating Scale (BPRS) score, the optimal therapeutic efficacy was found when the plasma concentrations of CBZ and CBZ-E were simultaneously set at 7 μg/ml ( r = 0.28, p = 0.19) and 1.4 μg/ml ( r = 0.78, p = 0.0001), respectively [ 17 ]. In this case, the values obtained in the previous study are more meaningful than those obtained in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a previous study, a similar result was found in a group of patients with bipolar disorder who were treated with CBZ [ 17 ]. As evaluated by the Brief Psychiatric Rating Scale (BPRS) score, the optimal therapeutic efficacy was found when the plasma concentrations of CBZ and CBZ-E were simultaneously set at 7 μg/ml ( r = 0.28, p = 0.19) and 1.4 μg/ml ( r = 0.78, p = 0.0001), respectively [ 17 ]. In this case, the values obtained in the previous study are more meaningful than those obtained in our study.…”
Section: Discussionsupporting
confidence: 81%
“…The plasma samples were analyzed with high-performance liquid chromatography in the Metabolic Biophysics, Professional Toxicology, and Applied Environmental Laboratory, Department of Biophysics, Medicine Faculty of Sousse, Sousse, Tunisia. The determination of the plasma levels of CBZ and CBZ-E in human plasma was conducted using previously described high-performance liquid chromatography (HPLC)-based assays [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic effect of CBZ was investigated using a wide range of concentrations from 1-1000 µM which cover all therapeutic, supra-therapeutic and toxic levels. The therapeutic level of CBZ was reported to be up to 12 mg/L (around 50µM), while the concentration of CBZ was reported to around 170 µM in cases of significant CBZ overdoses [32,33,34]. Higher concentrations were used to allow testing the chronic effect of the drug within the limited time frame of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of plasma samples were performed in the Laboratory of Metabolic Biophysics, Professional Toxicology and Applied Environnemental, Department of Biophysics, Medicine Faculty of Sousse, Sousse, Tunisia. Dosage of CBZ and CBZ-E was conducted using previously described high performance liquid chromatography [ 17 ].…”
Section: Methodsmentioning
confidence: 99%